Reliability of Prognostic and Predictive Factors Evaluated by Needle Core Biopsies of Large Breast Invasive Tumors. Issue 4 (1st October 2015) - Petrau, Camille; Clatot, Florian; Cornic, Marie; Berghian, Anca; Veresezan, Liana; Callonnec, Françoise; Baron, Marc; Veyret, Corinne; Laberge, Sophie; Thery, Jean-Christophe; Picquenot, Jean-Michel
Abstract: Objectives: Preoperative biopsy of breast cancer allows for prognostic/predictive marker assessment. However, large tumors, which are the main candidates for preoperative chemotherapy, are potentially more heterogeneous than smaller ones, which questions the reliability of histologic analyses of needle core biopsy (NCB) specimens compared with whole surgical specimens (WSS). We studied the histologic concordance between NCB specimens and WSS in tumors larger than 2 cm. Methods: Early pT2 or higher breast cancers diagnosed between 2008 and 2011 in our center, with no preoperative treatments, were retrospectively screened. We assessed the main prognostic and predictive validated parameters. Comparisons were performed using the κ test. Results: In total, 163 matched NCB specimens and WSS were analyzed. The correlation was excellent for ER and HER2 (κ = 0.94 and 0.91, respectively), moderate for PR (κ = 0.79) and histologic type (κ = 0.74), weak for Ki-67 (κ = 0.55), and minimal for SBR grade (κ = 0.29). Three of the 21 HER2-positive cases (14% of HER2-positive patients or 1.8% of all patients), by WSS analysis, were initially negative on NCB specimens even after chromogenic in situ hybridization. Conclusions: NCB for large breast tumors allowed reliable determination of ER/PR expression. However, the SBR grade may be deeply underestimated, and false-negative evaluation of the HER2 status would have led to a detrimental lack of trastuzumab administration.